SUBJECT SCOPE AND ARTISTRY OF N. FOZILOV’S STORIES (World Bulletin of Social Sciences, 2023)
As a result of this small research, we have considered the comments on the theme and art of the stories of Nasir Fazilov, one of the great representatives of Uzbek children's literature.